(untitled) (Journal of Business Management and Accounting, 2018)
Sound and effective capital structure is important for sustainable growth and development of any firm. This research work investigates the impact of capital structure on the financial performance of firms in Nigeria. A total of one hundred and six (106) non-financial firms listed on the Nigerian Stock Exchange between 2012 to 2016 were used as sample. Panel data for the selected firms were generated and analyzed using fixed effect model as a method of estimation. The dependent variable for the study is profitability which was measured as Return on Assets (ROA). The independent variables on the other hand are total debts to total assets (TD), total long term debts to total assets (LTD) and short term debts to total assets (STD) used independently. Sales Growth, Firm Growth and Firm Age are used as control variables. Results indicates a negative significant relationship between Total Debt to Asset, and short term debt with return on assets (ROA), on the other hand, an insignificant relationship between long term debt and return on assets.